Analisis Profitabilitas Usaha Tahu Tuna Krispi “Tatuchi” di Kecamatan Lowokwaru Kota Malang - Indah Dewi Surya; Candra Adi Intyas (Jurusan Sosial Ekonomi Perikanan, 2022)
Indonesia is an archipelagic country with huge potential for fishery resources. However, the level of fish consumption in Indonesia is relatively low compared to the potential of fishery resources owned. The causes of the low consumption of fish include the lack of public understanding about the benefits of consuming fish, the lack of smooth distribution of fish, and not optimal facilities and infrastructure. Researchers formulate a food innovation product derived from processed tuna, namely Tuna Crispy Tofu